Personality disorders and mystical experiences among artistically gifted young people - Radoń, Stanisław (Studia Psychologica: Theoria et praxis, 2009)
This article examines the role of the personality disorders on religious and mystical experiences among artistically gifted young people. Ss (N=150 aged 15-20 years) were administered questionnaire measures ten personality disorders (Radochońskis, Behavioral List) and eight of religious experience (Hood’s, Mysticism Scale). Multiple regression were used. The results of psychological analysis suggests that the personality disorders (by women - 6 disorders, by men - 2) are the important factors on religious and mystical experience (by women - 6 aspect of mystical experiences, by men - 2). Womens mystical experiences are influenced by higher intensification of schizotypal, borderline and obsessive-compulsive disorder and decrease intensification of dependent and histrionic disorder (3 clusters of disorders); mens - by decrease intensification of obsessive- compulsive and disorder (2 clusters).The results suggest that personality disorders may be important variables to consider within the theory of religious experience.